2015
DOI: 10.1111/disa.12137
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural disaster in individual and relational adjustment in Sri Lankan mothers following the 2004 tsunami

Abstract: The purpose of this study is to examine the associations between maternal mental health distress symptoms, including depression and post-traumatic stress disorder, the extent to which the presence of a child's disaster-related physical health problem(s) have interfered with daily functioning, and family cohesion over time among Sri Lankan mothers who survived the tsunami on 26 December 2004. Study variables were measured using a self-report questionnaire administered approximately four months after the event a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Our findings are a useful step towards developing a working understanding of distress in this population in two key areas: family adjustment and strain on the felt‐sense of being able to care for and support one's family. Consistent with earlier studies, our results showed negative associations between disaster‐related losses, perceived social support and indicators of family functioning (Banford et al, ; Wickrama & Kaspar, ; Wickrama & Wickrama, , ). Our results demonstrate greater damage from the tsunami was associated with lower efficacy in being able to care for one's family.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are a useful step towards developing a working understanding of distress in this population in two key areas: family adjustment and strain on the felt‐sense of being able to care for and support one's family. Consistent with earlier studies, our results showed negative associations between disaster‐related losses, perceived social support and indicators of family functioning (Banford et al, ; Wickrama & Kaspar, ; Wickrama & Wickrama, , ). Our results demonstrate greater damage from the tsunami was associated with lower efficacy in being able to care for one's family.…”
Section: Discussionsupporting
confidence: 92%
“…Examples of items include: house damage ; damage to consumer household items ; vehicles / boats ; animals / birds ; social order , norms and lawfulness ; local / village social organisations . Slightly differing versions of this scale has been used with tsunami‐affected population in Sri Lanka (Banford et al, ; Wickrama & Wickrama, ). In this sample the alpha for this scale was .82.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the particular organization and value on collective functioning in Sri Lanka make family relationships and social support paramount to understanding mental health (Wickrama & Wickrama, 2008). The concept of heavily valuing collectivism in families, sometimes referred to as familism (Portes & Rumbaut, 2001), has been explored as a resource and potential buffer in the effects of the tsunami on Sri Lankan survivors and has been evaluated as an outcome in research with disaster-affected communities (Banford et al, 2016).…”
Section: Adjustmentmentioning
confidence: 99%